Natural genetic variation in zinc (Zn) accumulation in Brassicaceae - Ó Lochlainn, Seosamh (2011)
Zinc (Zn) is an essential plant nutrient. Most plant species have a shoot Zn concentration ([Zn]shoot) <0.1 mg Zn g-1 dry weight (DW), but extensive natural genetic variation occurs. For example, within the Brassicaceae, some Noccaea (Thlaspi) and Arabidopsis species hyperaccumulate [Zn]shoot >10 mg Zn g-1 DW. There is compelling evidence that orthologues of the Arabidopsis thaliana PIB-type Heavy-Metal-Associated domain-containing ATPase 4 (AtHMA4), which transport Zn2+ and other cations, have a major involvement in the Zn hyperaccumulation trait. The aim of this thesis was to study aspects of genetic variation in the Brassicaceae using a comparative genomic approach, focussing primarily on orthologues of AtHMA4 in Noccaea and Brassica.